T-cell lymphoma in a ferret (Mustela putorius furo) - Ferreira, Vivian L.; Souza, Patrícia C.; Sueiro, Felipe A. R. (Brazilian Journal of Veterinary Pathology, 2010)
A 12 years old ferret was attended with clinical history of prostration and anorexia. The animal died a few hours after consultation. After necropsy, a histopathological exam of a liver tumor was carried out. The morphologic diagnosis was consistent with multicentric lymphoma. Immunohistochemical exam of the neoplastic cells was made additionally, and confirmed the diagnosis of T-cell lymphoma.